Cumulus cell acetyl-CoA metabolism from acetate is associated with maternal age but only partially with oocyte maturity. (2nd January 2022) - Anderson, Sharon; Xu, Peining; Frey, Alexander J.; Goodspeed, Jason R.; Doan, Mary T.; Orris, John J.; Clements, Nicolle; Glassner, Michael J.; Snyder, Nathaniel W.
ABSTRACT: Cumulus cell (CC) clumps that associate with oocytes provide the oocytes with growth and signaling factors. Thus, the metabolism of the CCs may influence oocyte function, and CC metabolism may be predictive of oocyte competence for in vitro fertilization. CCs are thought to be highly glycolytic, but data on the use of other potential carbon substrates are lacking in humans. This prospective and blinded cohort study was designed to examine the substrate utilization of CCs by age and oocyte competence. Individual sets of CC clumps from participants were removed after oocyte retrieval procedure then, incubated with stable isotope labeled substrates, and analyzed using liquid chromatography-high resolution mass spectrometry (LC-HRMS) for isotopologue enrichment of major metabolic intermediates, including acetyl-CoA. The acyl-chain of acetyl-CoA contains 2 carbons that can be derived from 13 C-labeled substrates resulting in an M + 2 isotopologue that contains 2 13 C atoms. Comparing the fate of three major carbon sources, mean enrichment of M + 2 acetyl-CoA (mean, standard deviation) was for glucose (3.6, 7.7), for glutamine (9.4, 6.2), and for acetate (20.7, 13.9). Due to this unexpected high and variable labeling from acetate, we then examined acetyl-CoA mean % enrichment from acetate in 278 CCs from 21 women ≤34 (49.06, 12.73) decreased with age compared to 124 CCs from 10 women >34 (43.48, 16.20) (p = 0.0004, t-test). The CCs associated with the immature prophase I oocytes had significantly lower enrichment in M + 2 acetyl CoA compared to the CCs associated with the metaphase I and metaphase II oocytes (difference: −6.02, CI: −1.74, -13.79, p = 0.013). Acetate metabolism in individual CC clumps was positively correlated with oocyte maturity and decreased with maternal age. These findings indicate that CC metabolism of non-glucose substrates should be investigated relative to oocyte function and age-related fertility. Abbreviations: CCs: cumulus cells; COC: cumulus-oocyte complex; LC-MS: liquid chromatography-mass spectrometry; acetyl-CoA: acetyl-Coenzyme A; CoA: Coenzyme A;